Composição botânica, estrutural, valor nutricional e dinâmica do nitrogênio em pastagens de azevém consorciadas - Skonieski, Fernando Reimann (2009)
The utilization of leguminous plants as a mixing with grass is an economic and simple alternative for the increment of nitrogen on soil and plants, building up the sustainability of pasture systems. This work aimed to evaluate the different species plants consorted with ryegrass through the N incidence on pastures, regarding the MS accumulation, within an agro ecological transition system. The experimental pasture was established by the minimum tillage of the soil after doing two harrowing. It was evaluated in the annual ryegrass culture (Lolium multiflorum Lam.), cv. Common and its treatment was composed joining black oats, white clover and forage peanut. The first grazing was done 21 days after the plants emerge in the pastures of AZ+AV and AZ+AF and 28 days after emerging in the pasture of AZ+TB. The second grazing, at the AZ|+AV pasture, occurred 30 days after the first one, whereas to the others, it occurred 37 days after. The rates of MS accumulation, considering the period of exclusion until the MS production hit the top, was 77,7, 75 and 71kg/ha of MS/day for the pastures joint with AZ+TB, AZ+AF and AZ+AV, respectively. The relation between leaf and culm, until the first grazing, was raised in every experiment. The coefficient (β), which was used in all the pasture samples, was lower than -0,60; the highest N concentration declination in plant tissues, as a consequence of the MS accumulation, occurred in the AZ+TB (-0,94) pasture sample and in the AZ+AF and AZ+AV pastures on the sequence, respectively. The highest content of N, in the plant tissue, was found in the ryegrass only when it was mixed up with white clover.